Effects of Depressive Disorder on Consumption of Tobacco in Brazil - Laís de Sousa Abreu Soares; Evandro Camargos Teixeira (Revista Facultad de Ciencias Económicas, 2025)
Tobacco use has detrimental effects on health, well-being, and productivity, making it a topic of interest across multiple scientific disciplines, including Economics. Economic research examines both the social and financial costs of tobacco consumption, as well as, how economic factors and public policies influence its demand. Emerging evidence also suggests a connection between tobacco use and mental health conditions. This study explores the impact of depressive disorders on the likelihood of tobacco use by employing a Bivariate Probit model. The findings reveal that individuals diagnosed with depression are significantly more likely to use tobacco products on a daily basis.